Gender and Transport Sector Employment: Evidence from Kogi State, Nigeria - Okon, Emmanuel O.; Richard, Shaibu H. (American Journal of Education and Learning, 2016)
The low employment of women in the transport sector is a trend that has been gradually reversing around the world; this paper seeks to ascertain the effectiveness of policies made to enhance women employment in transportation sector in Kogi State. Specifically, it attempts to examine why employers are still reluctant in employing women in transportation sector in Kogi state. Cross sectional survey design was used to obtain detailed data which were subjected to statistical analysis using several statistical tables and analytical tools. The results revealed that nursing mothers are not offered employment in the transportation sector. Most respondents agree that employers see women as inferior and do not fit in transportation sector. The result shows that government policy has no significant effect in enhancing women employment in transportation sector in Kogi state. Thus, this paper suggests that Kogi state government should ensure that its agencies or parastatals dealing with transport are made to address gender issues in transportation in terms of employment. As such it should consult with women’s associations, commissions and ministries on decision-making, implementation and monitoring of public policies applicable to transportation sector. Also, the state government should establish training programmes for women to learn how to operate public transit vehicles.